Comparative analysis of sentence order in Uzbek and English - Uktamova, Mokhigul; Sobirova, Rukhshona (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
This article analyzes the features of sentence order in the Uzbek language and its role in forming the meaning of a sentence. Sentence order ensures the clarity, logic and expressiveness of speech through the arrangement of parts of speech in a certain sequence. The article covers the main sentence order model characteristic of the Uzbek language - possessor + complement + case + participle - based on examples. The results of the work are important for the study of sentence order in Uzbek linguistics, for the analysis of practical speech and written texts.